Security motives and negative affective experiences during the early months of the COVID-19 pandemic. Issue 12 (2nd December 2022) - Rodrigues, David L.; Zoppolat, Giulia; Balzarini, Rhonda N.; B. Slatcher, Richard
Abstract: Objective: Self-regulation can help individuals cope during stressful events, but little is known about why and when this might occur. We examined if being more focused on prevention was linked to negative affective experiences during the COVID-19 pandemic. We also examined possible underlying mechanisms for this association, and whether social support buffered it. Design: Pre-registered longitudinal study, with surveys every 2 weeks over one month ( N = 1269). Main outcome measures: Regulatory focus and worry for health (T1), adherence to self-isolation and preventive health behaviours (T2), negative affective experiences, positive affect, frequency of online interactions, and perceived social support (T3). Results: Prevention focus was associated with health worries at baseline and linked to greater adherence to preventive health behaviours (T2). Only adherence to self-isolation was linked to more negative affective experiences (T3). Exploratory analyses showed that prevention focus was linked to more negative affective experiences (T3), but only for participants with fewer online interactions with their family and less perceived social support from family and friends. Conclusions: Prevention motives in threatening times can be a double-edged sword, with benefits for health behaviours and consequences for negative affective experiences. Having a strong social network during these times can alleviate these consequences.